Green tea polyphenols-whey proteins nanoparticles: Bulk, interfacial and foaming behavior - Rodríguez, Silvio David (2015)
The objective of the work was to study foaming and interfacial properties of β-lactoblobulin and caseinomacropeptide as affected by the formation of nano-particles with increasing amounts of green tea polyphenols. In this contribution foams were obtained by whipping and the overrun, liquid drainage and height stability of the foams were evaluated. The interfacial properties were determined by a drop tensiometer. The formation of nano-particles (30-90nm) decreased the surface pressure and the elastic component of the dilatational modulus of films that resulted in faster foam drainages. However, foam overrun was not affected and foam column falling was retarded. The results point out that nano-particles formed at low polyphenols concentration could retard foam falling without affecting foam overrun, despite decreasing the surface films viscoelasticity. The contribution of polyphenols to avoid foam column falling may be laid in the interfacial interactions between proteins and polyphenols.